Determination Young Athletes' in Improving Perfomance: Teamwork and Training Consistency (Literature Review Sport Education) - Reni Silviah (Siber Nusantara Review, 2025)
Literature review of teamwork determination, training consistency plays a role in athlete performance is a scientific article with the aim of analyzing whether athlete performance plays a role in teamwork and training consistency. Qualitative approach method with literature review method to explore and analyze the relationship between teamwork, training consistency, and athlete performance. The results of this article are: 1) Athlete performance plays a role in teamwork, 2) Athlete performance plays a role in training consistency. Apart from these 2 exogenous variables that affect the endogenous variable Athlete Performance, there are many other factors including discipline, character formation, physical activity.